PENGARUH KOMPENSASI NON FINANSIAL, PENEMPATAN, DAN KEMAMPUAN TERHADAP SEMANGAT KERJA KARYAWAN PADA PT. BANK PERKREDITAN RAKYAT UNISRITAMA - Yosi Yolanda; Susi Hendriani; Errin Yani Wijaya (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aims to determine how the effect of non-financial compensation, placement, and the ability of the employee morale at PT. Bank Unisritama. As for the population in this study were all employees that existed in the last PT. Bank Unisritama, ie 66 people. While the sampling is done by making all employees in the sample. Analysis of the data used is descriptive analysis with quantitative analysis tools that multiple linear regression with SPSS version 18.00. From the testing that has been done, simultaneous test (F-test) showed that non-financial compensation, placement and the ability to simultaneously significant effect on employee morale, while the partial test (t-test) showed that non-financial compensation, placement and the ability to partially significant effect on employee morale at PT. Bank Unisritama. To add to employee morale, Chairman of PT. Pekanbaru Unisritama Rural Banks should increase the sense of loyalty of employees in the work. For example by increasing the provision of non-financial compensation, put the employees in accordance with their expertise and seeks to train the ability of employees. It is expected to increase employee morale in the work. as well as the need to provide training opportunities to employees so that employee morale can be improved.Keyword : Non Financial Compensation, Placement, Ability and Work Spirit.